A Test Method for Acoustic Emission Properties of Natural Cellulose Fiber-Reinforced Composites - Liu, Fanxizi; Gao, Qiang; Guo, Hui; Lang, Chenhong; Jiang, Jinhua; Qiu, Yiping (Applied sciences, 2021)
To test the acoustic performance of fiber-reinforced composites for replacing wood, an acoustic vibration test method is developed. For evaluation of the test method, composites are manufactured using hemp and ramie embedded in epoxy, through vacuum-assisted resin infusion molding. The effects of the most important factors, i.e., impulse, relative humidity (RH), and specimen thickness, on the acoustic vibration response of the composites are systematically studied. The magnitudes of the impulses, represented by different masses of the dropping balls, seem to have little influence on the shapes of the acoustic vibration curves, although the intensity of the spectra increases as the impulse increases. The RH influences the spectrum shape significantly due to variation in the Young’s modulus and density of the material upon absorption of moisture. The specimen thickness also greatly affects the testing results. The specific dynamic modulus, acoustic radiation damping coefficient, and acoustic impedance change a little as the impulse magnitude and RH change, but decrease substantially as the specimen thickness increases. The specific dynamic modulus can be linearly correlated with the flexural modulus of a material.